2019
DOI: 10.1029/2019gl084123
|View full text |Cite
|
Sign up to set email alerts
|

Ross Ice Shelf Icequakes Associated With Ocean Gravity Wave Activity

Abstract: Gravity waves impacting ice shelves illicit a suite of responses that can affect ice shelf integrity. Broadband seismometers deployed on the Ross Ice Shelf, complemented by a near‐icefront seafloor hydrophone, establish the association of strong icequake activity with ocean gravity wave amplitudes (AG) below 0.04 Hz. The Ross Ice Shelf‐front seismic vertical displacement amplitudes (ASV) are well correlated with AG, allowing estimating the frequency‐dependent transfer function from gravity wave amplitude to ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 37 publications
6
43
0
Order By: Relevance
“…Nevertheless, we note that the icy shell of Enceladus is likely to be both seismically quieter (due to a lack of atmospheric and surface ocean processes) and less attenuative (due to much lower temperatures; ∼−198°C) than the Ross Ice Shelf. Olinger et al (2019) and Chen et al (2019) showed that the rift WR4 is seismically active, and here we have here demonstrated that rift WR6 is seismogenic as well. Both rifts are seaward of the ice shelf compressive arch induced by the marginal stresses of the flowing ice shelf (which advects seaward at speeds in excess of 1 km/year near its ocean edge) and thus experience a background laterally biaxial extensional stress field (e.g., Lipovsky, 2020).…”
Section: Tablesupporting
confidence: 77%
“…Nevertheless, we note that the icy shell of Enceladus is likely to be both seismically quieter (due to a lack of atmospheric and surface ocean processes) and less attenuative (due to much lower temperatures; ∼−198°C) than the Ross Ice Shelf. Olinger et al (2019) and Chen et al (2019) showed that the rift WR4 is seismically active, and here we have here demonstrated that rift WR6 is seismogenic as well. Both rifts are seaward of the ice shelf compressive arch induced by the marginal stresses of the flowing ice shelf (which advects seaward at speeds in excess of 1 km/year near its ocean edge) and thus experience a background laterally biaxial extensional stress field (e.g., Lipovsky, 2020).…”
Section: Tablesupporting
confidence: 77%
“…A flow-normal gradient in interannual velocity difference was observed between DR10 and DR14, located on opposite sides of a major east–west trending rift and separated by 20 km (Figs 1a and 5, Section 4.2). This flow-normal gradient may result from rift activity associated with shear stresses along the nearby rift tip near the suture zone, and with enhanced ice-quake activity in that region (Chen and others, 2019; Olinger and others, 2019). The incoherent anomaly observed at the three ice-front stations (DR01, DR02 and DR03) could also be explained by local calving events and/or variable near-front melting that perturbs the general ice-flow pattern along the front.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the major impact of sea ice in this analysis is that it prohibits wind observations, rather than distorting the observed wave event on its travel path. Sea ice attenuates higher‐frequency swell (Ardhuin et al, ; Bates & Shapiro, ; Chen et al, ; Hell et al, ; Squire & Allan, ; Squire, ; Stopa et al, ), while wave dispersion changes are minor for typical mean sea ice thicknesses of about 1.5 m in the Southern Ocean Gyres and for periods longer than 15 s (Wadhams & Doble, ; Williams et al, ). This analysis only uses the dispersion of linear deep ocean waves, so the attenuation of waves in sea ice has no effect on the analysis, as long as wave‐induced signals are detected by seismometers.…”
Section: Discussionmentioning
confidence: 99%
“…We show here (i) that this method can be used to validate state‐of‐the‐art reanalysis products (section ) and (ii) that swell from storms travels through the sea ice and impacts the Ross Ice Shelf. The methodology provides a means to verify ocean wave products and to examine both sea ice‐wave interactions and the impact of ocean swell on ice shelves (Chen et al, ; Massom et al, ; Ren & Leslie, ).…”
Section: Introductionmentioning
confidence: 99%